1972
DOI: 10.1063/1.1678092
|View full text |Cite
|
Sign up to set email alerts
|

Computed Bond Energies and Vibrational Frequencies for ClHCl, BrHBr, and IHI, Including Isotope Effects and Anharmonicity

Abstract: The bond-energy-bond-order (BEBO) method of Johnston and Parr predicts ClHCl, BrHBr, and IHI are all bound and symmetric. When corrected for anharmonicity of the asymmetric stretch normal mode, it predicts the following vibrational frequencies in cm−1 (experimental results are in parentheses; s is the symmetric stretch and a is the asymmetric stretch): ClHCl, s: 371 (259); ClDCl, s: 370 (265), a: 318 (463); BrHBr, s: 222 (165), a: 533 (727); BrDBr, s: 222 (170), 442 (496); IHI, s: 165 (121), a: 862 (686); IDI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Calculations of these saddle-point properties (see Table I) from the potential energy surface parameters reported reveals that Wilkin's surface has a reaction barrier height of 22.4 kcal/mole and Thompson's a reaction barrier height of 27.8 In contrast, the empirical bond energy-bond order (BEBO) method [ 181 predicts E b = 5.5 kcal/mole for FHF(Q), which is more in harmony with the chemical kinetics experience noted above [13]. In view of the success evidenced by the B E 3 0 method in predicting (1) activation energies for a wide variety of hydroyen atom transfer reactions [ 18,191, (2) saddle-point properties and minimum energy reaction paths for H + H z and F + Hz in agreement with a b initio calculations (20), and (3) stable X H X radicals ( X = I, Br, Cl) and their vibrational frequencies, which are in reasonable accord with experiment [21], the lower E b predicted by the BEBO method cannot be dismissed lightly. We have therefore carried out quasi-classical trajectory calculations of the vibrational relaxation of HF(o = 1) by F atoms on a potential energy surface calibrated so that the reaction barrier height agrees with the BEBO prediction in order to ascertain whether (1) the resulting 1 + 0 vibrational relaxation rate coefficient is also compatible with the experimental measurements [ 1, 2,6,7], and (2) chemical effects, e.g., reaction (l), provide an efficient mechanism for vibrational relaxation at room temperature.…”
Section: Introductionsupporting
confidence: 65%
“…Calculations of these saddle-point properties (see Table I) from the potential energy surface parameters reported reveals that Wilkin's surface has a reaction barrier height of 22.4 kcal/mole and Thompson's a reaction barrier height of 27.8 In contrast, the empirical bond energy-bond order (BEBO) method [ 181 predicts E b = 5.5 kcal/mole for FHF(Q), which is more in harmony with the chemical kinetics experience noted above [13]. In view of the success evidenced by the B E 3 0 method in predicting (1) activation energies for a wide variety of hydroyen atom transfer reactions [ 18,191, (2) saddle-point properties and minimum energy reaction paths for H + H z and F + Hz in agreement with a b initio calculations (20), and (3) stable X H X radicals ( X = I, Br, Cl) and their vibrational frequencies, which are in reasonable accord with experiment [21], the lower E b predicted by the BEBO method cannot be dismissed lightly. We have therefore carried out quasi-classical trajectory calculations of the vibrational relaxation of HF(o = 1) by F atoms on a potential energy surface calibrated so that the reaction barrier height agrees with the BEBO prediction in order to ascertain whether (1) the resulting 1 + 0 vibrational relaxation rate coefficient is also compatible with the experimental measurements [ 1, 2,6,7], and (2) chemical effects, e.g., reaction (l), provide an efficient mechanism for vibrational relaxation at room temperature.…”
Section: Introductionsupporting
confidence: 65%
“…We have not attempted comparisons between the C1 3 properties predicted by the surface obtained from the parameters in Table I and the matrix isolation experimental data. Truhlar et al 29 and Porter et al 6 have made such comparisons for XHX (X = halogen) using surfaces of the same formulation as the present; they found some lack of agreement between experiment and theory. We would expect no better result for the present case.…”
Section: B Discussionmentioning
confidence: 60%
“…Some authors have used surfaces with high barriers, for example, Eb =33.9 kJ mo1-1 for a modified LEPS formalism [51] or Eb=41.2 , 29.5 and 26.0 kJ mo1-1 [52,53] for LEPS surfaces. Other authors have suggested surfaces with wells, for example, Ew = -3.22 kJ mo1-1 [54], -6.53 kJ mo1-1 [55] and -20.6 kJ mol -t [56]. Smith [57] has carried out quasiclassical trajectory calculations on 5 LEPS surfaces having Eb=26.0 , 7-9, 4-15, 0.06kJmo1-1 and Ew=-25"9 kJ mo1-1.…”
mentioning
confidence: 99%